Behaviour of oxygen transfer in a simulated multiphase hydrocarbon-based bioprocess in a bubble column reactor - Abufalgha, Ayman A. (Stellenbosch : Stellenbosch University, 2018)
Thesis (MEng)--Stellenbosch University, 2018.